African Continental Free Trade Area as a Lever for Economic Diversification in Algeria (Journal of Economic Additions, 2026)
This study examines the role of AfCFTA in advancing Algeria’s economic diversification and reducing dependence on hydrocarbons. Through a descriptive-analytical approach, it assesses opportunities to boost non-oil exports—particularly in manufacturing, agriculture, food processing, services, and logistics—while addressing internal constraints (weak competitiveness, bureaucracy, limited innovation and financing) and external challenges (regional competition, technical standards, transport issues). It concludes that AfCFTA presents a strategic opportunity, contingent on stronger competitiveness and effective export-support policies.Jel Classification Codes : O11 ; O55 ; F15.
Keywords: Regional Economic Integration; Intra-African Trade; Non-Oil Exports; Economic Development.